İkinci dünya savaşı döneminde İstanbul’ un sosyo ekonomik yapısı - Gedik, Orhan (My University, 2001)
Tezi üç ana bölüme ayırdım. Bunlar; Uygulanan Politikalar, Sosyal Yapı ve Ekonomik Yapı idi. Birinci bölümde bu dönemde çıkarılan kanunlardan ve hükümet programlarından bahsederek sıkıntılardan kurtulmak için o dönem yöneticilerinin yaptıkları anlatıldı. Bu bölümdeki en önemli bölüm Varlık Vergisi ve sonuçlarıdır. İkinci Bölümde Nüfus, yerleşim, Ulaşım, Sosyal Guruplar ilişkisi , Kültürel ve Eğitim alanındaki çalışmalar ele alındı. Bu bölümün en önemli kısmı Nüfus ve Göç konusu ile Sosyal Guruplar İlişkisi oldu. Özellikle Sosyal Guruplar İlişkisi bu dönemdeki birçok problemin de nedenlerini ortaya koyması açısından önemli bir yer tutmaktadır. Üçüncü ve son bölümde Ekonomik Yapı üzerinde duruldu. Tarım, Ticaret ve Sanayi olarak bölümlere ayrıldı. Bu bölümde Sanayi konusu biraz daha dikkatli bir şekilde ele alındı. Türkiye, İkinci Dünya Savaşına fiilen girmemiş olsa bile bunun sosyal ve ekonomik sonuçlarını en ağır biçimde yaşadı. Hatta bu dönemdeki birçok problem günümüzdeki problemlerin de temelini teşkil etti. Hastalığın tedavisi için öncelikle bunun nereden geldiğinin bilinmesi gerektiği gibi bu sıkıntıların da çözülebilmesi için öncelikle ne şekilde hangi şartlarda ortaya çıktığının bilinmesi gerektiğini düşündüm. Bu tezi yeni dönemdeki problemlere çözüm arayanlara küçük çapta da olsa bir ışık olması amacıyla sundum.

If I study on or choose asubject, I think that it's necessary to responce the chaes trouble in recent time. I wish to get a subject related to the recent term. Unless we don't understand the base, it's impossible to understantd these days so I have chosen the subject of master piece called the function of Socio - economic in İstanbul during the second Word War. As İstanbul is one of the main parts of Turkey, by understanding İstanbul one can olso understand Turkey. In fact, I aimed to deol with the lestest period an com bine it with nowadays. I wished it to be a preparetion for oters eventhough can't succed it y şelf. Since there isn't a specific source about this subject I applied to various sources, I divided y thesis into theree main parts: Applied Politics, Social Structure and Economic Structure. In the first part, I dealt with the laws made in that period and the politics applied, so I told about the solutions for the trobles of tihe time. The main part of tihis section is incoine tax and its results. The second part contains population, residence, transportation, social groups and the relationship among tehm. Studies in cultural and etduratiional areas were also handeled. The most important par of tihis sectiion tis the connection between social groups, immigration anda population. Especially the social group is tihe most important part because it reveals the sources of the problems of the tay. In the third and the last part of the thesis, the economic structure is handled. İt's divided into the parts as, agriculture, trade and industry. In tihs part the matter of industry is dealt with more carefully. Türkey was badly affected by the results of World War II although she didn't take part in the war actively, Moreover many of the problems of the days are the sourcesof the today's problems. First, one should identify a disease to be able to cure it. Just like tahat, we should understand teh troubles and their reasons to be able to find solutions for them. I preparec this thesis just to give a perspective for the ones who are lookiye for solitions to the current problems.
Keywords: Dünya Savaşı 2 1939-1945; Iktisat Tarihi-Türkiye; Istanbul Tarih